Persistency and Money Demand Distortions in a Stochastic DGE Model with Sticky Prices and Capital - Michael Gail (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2002)
This paper considers the implications of adding capital as a factor of production in a stochastic DGE model with sticky prices. Particular attention is given to the role of money demand and to the form of the utility function. I consider cash-in-advance- (CIA) as well as money-in-the-utility-function- (MIU) models, with CRRA and GHH preferences, to evaluate their ability to generate persistence. It is shown that even in a MIU-model with a GHH utility function and a high elasticity of labor supply with respect to the real wage the additional intertemporal substitution channel opened through capital accumulation does have a significant dampening influence on the persistence effects of monetary shocks. In a CIA-setup with GHH preferences the model can generate the liquidity effect. A multiplicatively separable CRRA utility function in the MIU-model cannot account for the observed persistent reactions of inflation and output either.
Keywords: E52; 330; Monetary Policy; New Neoclassical Synthesis; Sticky Prices; Persistency; Neue klassische Makroökonomik; Geldnachfragetheorie; Real Business Cycle; Preisrigidität; Dynamisches Gleichgewicht; Geldpolitik; Schock; Hysteresis; Theorie; Makroökonomischer Einfluss